2004
DOI: 10.1016/s0014-5793(03)01527-8
|View full text |Cite
|
Sign up to set email alerts
|

PPARγ mediates NSAIDs‐induced upregulation of TFF2 expression in gastric epithelial cells

Abstract: Trefoil factor family (TFF) is a group of peptides that play critical roles in maintaining gastric mucosal integrity. In real-time quantitative reverse transcription-polymerase chain reaction (RT-PCR) and reporter gene assays, we show that indomethacin and aspirin upregulate TFF2 expression in MKN45 gastric cells. These drugs also activated peroxisome proliferator-activated receptor Q Q (PPARQ Q) at concentration ranges that increase TFF2 expression, and upregulated TFF2 expression was suppressed by GW9662, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 30 publications
2
15
0
Order By: Relevance
“…Regulation of TFF2 by gastrin may play a role in the protection and repair of the gastrointestinal mucosa [35]. Besides, although non-steroidal anti-inflammatory drugs (NSAIDs) has no notable effect on the expression of TFF1 and TFF3 mRNA, it upregulates TFF2 mRNA expression through activation of peroxisome proliferator-activated receptor γ (PPAR γ) in a dose-and time-dependent manner [88,89] (Table 2). This mechanism may be important in reducing the extent of gastric mucosal damage caused by the administration of NSAIDs [89].…”
Section: Gastrin Nsaids and Gos Upregulate The Expression Of Tff2/ Tff3mentioning
confidence: 99%
See 1 more Smart Citation
“…Regulation of TFF2 by gastrin may play a role in the protection and repair of the gastrointestinal mucosa [35]. Besides, although non-steroidal anti-inflammatory drugs (NSAIDs) has no notable effect on the expression of TFF1 and TFF3 mRNA, it upregulates TFF2 mRNA expression through activation of peroxisome proliferator-activated receptor γ (PPAR γ) in a dose-and time-dependent manner [88,89] (Table 2). This mechanism may be important in reducing the extent of gastric mucosal damage caused by the administration of NSAIDs [89].…”
Section: Gastrin Nsaids and Gos Upregulate The Expression Of Tff2/ Tff3mentioning
confidence: 99%
“…Besides, although non-steroidal anti-inflammatory drugs (NSAIDs) has no notable effect on the expression of TFF1 and TFF3 mRNA, it upregulates TFF2 mRNA expression through activation of peroxisome proliferator-activated receptor γ (PPAR γ) in a dose-and time-dependent manner [88,89] (Table 2). This mechanism may be important in reducing the extent of gastric mucosal damage caused by the administration of NSAIDs [89]. In addition, after treating with prebiotic galacto-oligosaccharides (GOS), the expressions of MUC2 and TFF3 are significantly up-regulated (Table 2), which indicates that GOS may enhance mucosal protective function via direct stimulation of intestinal goblet cells [90].…”
Section: Gastrin Nsaids and Gos Upregulate The Expression Of Tff2/ Tff3mentioning
confidence: 99%
“…Both prostaglandins and trefoil peptides have cytoprotective functions in the gastric mucosa [44,45], and it has been suggested that the actions of these two families may be linked [46]. A common linkage may be one or more members of the prostaglandin and peroxisome proliferator-activated receptors (PPARs) transcription factor family of nuclear receptors, which are involved in modulating cell growth, differentiation and infl ammation in the gut and elsewhere [47,48].…”
Section: Prostaglandins and Peroxisome Proliferatoractivated Receptorsmentioning
confidence: 99%
“…A common linkage may be one or more members of the prostaglandin and peroxisome proliferator-activated receptors (PPARs) transcription factor family of nuclear receptors, which are involved in modulating cell growth, differentiation and infl ammation in the gut and elsewhere [47,48]. The PPARg receptor in particular has been shown to be expressed by the normal gastric mucosa, and gastric cancer cell lines, and the PPARg ligands 15d-PGJ 2 and troglitazone (TGZ), act to suppress DNA synthesis in these cells and also upregulate both TFF1 and TFF2 mRNA in a dose-dependent fashion [46,49]. Evidence has been presented that the previously observed stimulatory effects of non-steroidal anti-infl ammatory drugs (NSAIDs) on TFF2 gene transcription in cell lines [50,51] may be mediated by a direct effect of these drugs on PPARg, since both indomethacin and aspirin stimulate PPAR-luc transcription, which can be blocked by the PPARg inhibitor GW9662 [46].…”
Section: Prostaglandins and Peroxisome Proliferatoractivated Receptorsmentioning
confidence: 99%
See 1 more Smart Citation